Role of ursolic acid in preventing gastrointestinal cancer: recent trends and future perspectives - Chauhan, Abhishek; Pathak, Vinay Mohan; Yadav, Monika; Chauhan, Ritu; Babu, Neelesh; Chowdhary, Manish; Ranjan, Anuj; Mathkor, Darin Mansor; Haque, Shafiul; Tuli, Hardeep Singh; Ramniwas, Seema; Yadav, Vikas (Frontiers in Pharmacology, 2024)
Gastrointestinal malignancies are one of the major worldwide health concerns. In the present review, we have assessed the plausible therapeutic implication of Ursolic Acid (UA) against gastrointestinal cancer. By modulating several signaling pathways critical in cancer development, UA could offer anti-inflammatory, anti-proliferative, and anti-metastatic properties. However, being of low oral bioavailability and poor permeability, its clinical value is restricted. To deliver and protect the drug, liposomes and polymer micelles are two UA nanoformulations that can effectively increase medicine stability. The use of UA for treating cancers is safe and appropriate with low toxicity characteristics and a predictable pharmacokinetic profile. Although the bioavailability of UA is limited, its nanoformulations could emerge as an alternative to enhance its efficacy in treating GI cancers. Further optimization and validation in the clinical trials are necessary. The combination of molecular profiling with nanoparticle-based drug delivery technologies holds the potential for bringing UA to maximum efficacy, looking for good prospects with GI cancer treatment.